Frequently cutting restriction enzymes: Clearing the fog to see the ends - Vaquero-Sedas, María I.; Vega-Palas, Miguel A. (Scientific Research Publishing, 2013)
Telomeres, which are found at the ends of eukaryotic chromosomes, are composed of tandem arrays of repetitive sequences and safeguard genomic stability. Previous studies have revealed that telomeric repeats are also present at internal chromosomal loci in many eukaryotes. However, the biological role of these interstitial telomeric sequences (ITSs) remains unknown. The integrity of telomeric length and chromatin structure is required for telomere stability. However, the study of these telomeric features can be impeded by the presence of ITSs. Frequently cutting restriction enzymes have been revealed to be very useful tools for the study of the length and chromatin structure of telomeres independent of the presence of ITSs.
Keywords: Telomeric Length; Telomeric Chromatin Structure; Frequently Cutting Restriction Enzymes; Arabidopsis thaliana